(untitled) (African Journal of Dairy Farming and Milk Production, 2017)
A total of 564 serum samples were randomly collected from 29 farms located in the nine main dairying districts in China’s north-eastern Heilongjiang Province from 2009 to 2010, and the seroprevalence of antibodies against COXIELLA BURNETII was determined by indirect enzyme-linked immunosorbent assay (ELISA). The average seroprevalence of C. BURNETII in dairy cattle was 10.1% (57/564). The seroprevalence of C. BURNETII in aborting cows (11.6%) was higher than that in non-aborting cows (5.1%). Dairy cows aged 3 years had the highest seroprevalence (20.5%), followed by dairy cows aged 4 years (14.3%). Dairy cows in their first pregnancy had the highest seroprevalence (25.8%). There was an apparent association between C. BURNETII seropositivity and abortion, age, and number of pregnancies (P < 0.05). The results of the present survey indicate that C. BURNETII infection in dairy cows is widespread in Heilongjiang Province, and it may be one of the most major causes of dairy cow abortion.